2021
DOI: 10.2147/clep.s314020
|View full text |Cite
|
Sign up to set email alerts
|

Current Practices in Missing Data Handling for Interrupted Time Series Studies Performed on Individual-Level Data: A Scoping Review in Health Research

Abstract: Objective Missing data can produce biased estimates in interrupted time series (ITS) analyses. We reviewed recent ITS investigations on health topics for determining 1) the data management strategies and statistical analysis performed, 2) how often missing data were considered and, if so, how they were evaluated, reported and handled. Study Design and Setting This was a scoping review following standard recommendations from the PRISMA Extension for Scoping Reviews. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, most of the studies did not mention the missing data. A study mentioned that most of the study used data aggregated at the population level, but it will lead to bias when data are missing at random at the individual level [ 11 ]. In a simulated scenario in this study, if the outcome is missing at random for male but is fully observed for female, the aggregated data will show a wrong seasonal pattern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, most of the studies did not mention the missing data. A study mentioned that most of the study used data aggregated at the population level, but it will lead to bias when data are missing at random at the individual level [ 11 ]. In a simulated scenario in this study, if the outcome is missing at random for male but is fully observed for female, the aggregated data will show a wrong seasonal pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have systematically reviewed methodological issues regarding the design and statistical analysis of the ITS study [ 11 , 21 25 ]. All of the previous reviews pointed out that the considerations of autocorrelation, non-stationary and seasonality were limited, which was aligned with our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations